PKM PEMANFAATAN TEKNOLOGI POMPA SUBMERSIBLE DI DESA PADANGDANGAN KECAMATAN PASONGSONGAN KABUPATEN SUMENEP JAWA TIMUR - Sutrisno, Adi; Mustakim, '; andayani, sri (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2018)
Padangdangan Village is one of the villages that lacks irrigation water when the dry season arrives. This is caused by the soil structure is included in dry land which can only be planted with corn, once a year. Padangdangan villagers rarely have their own toilets, so for the need to defecate, most villagers do it in open fields. This causes an outbreak of unwanted diseases. With this problem, the PKM program was offered entitled "PKM utilization of Submersible Pumps in Padangdangan Village, Pasongsongan, Sumenep ". The installation of the Submersible pump is expected to solve the problem of the Kelompok Tani Adi and the Kelompok Tani Adi Rasa in Padangdangan Village for the difficulty of procuring irrigation water. So that the two farmer groups can have other options in farming which will have an impact on quality and a better standard of living. This pump is suitable because the pump is free of noise, has a natural cooling system, and is safe from thieves.